Konsep Rahn Dan Implementasinya Di Indonesia - Meirani Rahayu Rukmanda (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2020)
Al-Quran and al hadith are the main sources of teaching for Muslims in navigating life in this world, therefore we as Muslims are very important to study and study and even study comprehensively and not partially as well as the theme of the paper which will be discussed this time, namely Regarding Ar-rahn as one of the rules in ber Muamalah, there are a lot of lessons that we will get from the existence of this Ar-rahn rule or pawning in muamalah, one of which is to strengthen trust between fellow business actors as well as people who are entangled with urgent economic conditions or lack of funds and for the sake of their survival, it is very important to comprehensively study the interpretation and hadith about Arrahn.